Шляхи вирішення проблем фінансового забезпечення соціальних виплат в Україні - Кулай, Аліна Василівна; Гром, Василь Андрійович; Kulaj, A. V.; Grom, V. A. (Волинський національний університет імені Лесі Українки, 2008)
У статті висвітлено особливості чинного фінансового механізму соціальних виплат, проаналізовано проблеми їх організації та запропоновано шляхи можливого вирішенняThe Problems of the Financial Ensuring of the Social Payments in Ukraine and the Ways of Their Resolving. In this article are elucidated the peculiarities of the acting financial mechanism of the social payments, are analyzed the problems of their organization and are offered the ways of their possible resolving.
The Problems of the Financial Ensuring of the Social Payments in Ukraine and the Ways of Their Resolving
Keywords: social payment; privilege; subsidy; financial mechanism; соціальні виплати; пільги; субсидії; фінансовий механізм